THE APPLICATION OF THE BAHTSUL MASA'IL METHOD TO INCREASE STUDENTS' CRITICAL POWER IN JURISPRUDENCE LESSONS AT MA MIFTAHUL ULUM AN-NUR PROBOLINGGO - Sya'diyah, Halimatus (Media Inovasi Pendidikan dan Publikasi, 2025)
One of the efforts made by educational institutions to create students who have critical thinking power is to provide a forum for studying religious problems found in society, which is carried out using the bahtsul masa'il learning method which will train students' critical thinking towards finding and solving various problems of social life in society. Given the urgency of this learning, researchers are interested in conducting research on the application of the bahtsul masa'il method to increase students' critical thinking in fiqh learning at MA Miftahul Ulum An-Nur Probolinggo. The focus of this research is (1) How is the application of the bahstul masa'il method to improve the critical thinking of grade XI students in fiqh learning at MA Miftahul Ulum An-Nur Probolinggul masa'il? (2) what are the supporting and inhibiting factors in the application of the bahtsul masa'il method to improve the critical thinking of grade IX students in fiqh learning at MA Miftahul Ulum An-Nur?. The purpose of this study is to describe the application of learning and inhibitors and supporters of the application of the bahstul masa'il method in fiqh learning in an effort to increase students' critical thinking in fiqh learning. To identify these problems, this research uses data collection techniques using a descriptive qualitative approach with the type of field research. The data collection in this research is observation, interview and documentation. While analyzing data collection, data condensation, data presentation and conclusion drawing. Based on the research obtained a conclusion (1) the application of the bahtsul masa'il method to increase students' critical thinking in fiqh learning at MA Miftahul Ulum An-Nur probolinggo, namely being able to identify problems, being able to express opinions and being able to solve problems and in the application of this bahsul masail method the stratgei applied is to familiarize students to be independent by giving a problem and looking for answers themselves based on their respective groups, fulfilling student facilities in the form of a library. (2) The supporting factors are the full motivation given by the caregiver, the students have learned the science of tools and other books, they argue according to what has been taught by the kiayi and ustda when studying the book. The inhibiting factors are less than optimal human resources, inadequate references, and insufficient time